Android Based Shoe Laundry Ordering Service System Using Google API Waru, Sidoarjo - Hendra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2021)
Lifestyle is a secondary need in human life, which changes depending on the times or a person's desire to change his lifestyle. Along with the development of life style many people choose to want something that is practical and does not impose himself, for example, people who are lazy to wash clothes, shoes and others because far from home, make a lot of people who took the initiative to make services of laundry or the laundry for profit of the job. So a research was conducted on android-based shoe wash ordering services in the Waru area, Sidoarjo. The purpose of this study is to facilitate and assist small entrepreneurs in obtaining customers and to assist users of laundry shoeand shoe repair services in finding locations and using the services of these entrepreneurs. The research was conducted using the SDLC (methodSoftware Development Life Cycle). Where SDLC is a system development methodology to compile a new system to replace the old system, update or improve the existing system. To deal with this, anservice ordering application is created laundry android based shoeto help entrepreneurs and the community. This application is used by using theprogramming language Java along with MySQL database. The results of a survey given to 10 people, get 75% results which state that the application is quite helpful and satisfying.